2010
DOI: 10.1063/1.3455207
|View full text |Cite
|
Sign up to set email alerts
|

A femtosecond velocity map imaging study on B-band predissociation in CH3I. I. The band origin

Abstract: A femtosecond pump-probe experiment, coupled with velocity map ion imaging, is reported on the second absorption band (B-band) of CH(3)I. The measurements provide a detailed picture of real-time B-band predissociation in the band origin at 201.2 nm. Several new data are reported. (i) A value of 1.5+/-0.1 ps has been obtained for the lifetime of the excited state, consistent within errors with the only other direct measurement of this quantity [A. P. Baronavski and J. C. Owrutsky, J. Chem. Phys. 108, 3445 (1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
121
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(156 citation statements)
references
References 38 publications
31
121
4
Order By: Relevance
“…23 The time-resolved work of Baronavski and Owrustky 10 provided the first direct measurements of the lifetimes of many vibrational levels of the B-band and concluded that the lifetimes could be as extreme as 200 fs (for the ν 6 = 2 level) and 4100 fs (for the ν 3 = 1 level). Even though the lifetime found for the vibrationless level has been measured recently [15][16][17] and found in agreement with Baronavski and Owrustky's value, no other measurement of the lifetimes for the rest of the vibronic levels has been reported. We partially cover this matter in this work with measurements of the lifetimes of the ν 2 = 1 and ν 3 = 1 levels through a variety of time-resolved techniques.…”
Section: -9supporting
confidence: 60%
See 3 more Smart Citations
“…23 The time-resolved work of Baronavski and Owrustky 10 provided the first direct measurements of the lifetimes of many vibrational levels of the B-band and concluded that the lifetimes could be as extreme as 200 fs (for the ν 6 = 2 level) and 4100 fs (for the ν 3 = 1 level). Even though the lifetime found for the vibrationless level has been measured recently [15][16][17] and found in agreement with Baronavski and Owrustky's value, no other measurement of the lifetimes for the rest of the vibronic levels has been reported. We partially cover this matter in this work with measurements of the lifetimes of the ν 2 = 1 and ν 3 = 1 levels through a variety of time-resolved techniques.…”
Section: -9supporting
confidence: 60%
“…Even stronger uncertainty remained as to the nature of the products of the predissociation process as a function of the vibronic level initially excited, since very scarce information is available on the matter, and it concerns only either the band origin [15][16][17] or the 2 2 0 band, since this last one can be accessed through the well known ArF laser transition at 193.3 nm. 19,24 Theoretical information is also scarce, the most valuable source at present being the very recent 1D work by Alekseyev et al 18 The experimental results that will be shown in this paper tackle the two main issues of importance: the degree and nature of vibrational excitation in the methyl fragment resulting from the predissociation process, and whether the branching ratio between the spin-orbit excited and the ground-state iodine channels, defined as *=[I*]/([I] + [I*]), is unity or less than unity.…”
Section: -9mentioning
confidence: 99%
See 2 more Smart Citations
“…CH 3 I, a symmetric top molecule, has been used extensively to study the ionization and dissociation dynamic process [1][2][3]. Recently, the interaction of nanosecond laser with CH 3 I cluster was investigated widely, where multiply charged ions with high energy were observed experimentally [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%